Parental and Peer Group Influence on Adolescent’s Behavior - Dhanada Mazumdar (International Journal of Advanced Science and Technology, 2020)
This present study mainly aimed to uncover How parents and peer groups influence the behavior of adolescents. Parents and peer groups work as the primary agents of socialization in every individual’s life and both the agents have crucial role in shaping of behavior of adolescent. As the key members of a family parents influence the behavior attitude, interest and overall personality of their adolescent. Again peer groups provide a sense of belongingness emotional security, environment of equality and freedom. At the same time peer groups may be proved as deliriant also to the adolescents. This study help to understand How peer groups and the parents influence the adolescents in behavioral aspect directly or indirectly and positively or negatively. This study is mainly based on reviewing of existing literature such as books, journal papers, reports, websites etc. Various research studies have documented that peer groups and parental influence may be the dominant factor of many behavioral issues in adolescent. Finally, the investigator proposed some recommendation for dealing with the issues related to the behavior of adolescent.